2023
DOI: 10.1371/journal.pone.0282835
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant extended spectrum β-lactamase (ESBL)-producing Escherichia coli from farm produce and agricultural environments in Edo State, Nigeria

Abstract: Antimicrobial resistance (AMR) is a major public health concern, especially the extended-spectrum β-lactamase-producing (ESBL) Escherichia coli bacteria are emerging as a global human health hazard. This study characterized extended-spectrum β-lactamase Escherichia coli (ESBL-E. coli) isolates from farm sources and open markets in Edo State, Nigeria. A total of 254 samples were obtained in Edo State and included representatives from agricultural farms (soil, manure, irrigation water) and vegetables from open m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The occurrence of ESBL producing Enterobacteriaceae isolates in our study suggest that the enzymes may be responsible for β-lactam resistant isolates were ESBL producers and this suggest that the resistant to β-lactam may be due to other mechanism like modification of target site of β-lactam or decrease in cellular uptake of the antibiotics. The percentage occurrence of ESBL producing Escherichia coli (36.36%) was lower than 68% Igbinosa et al (2023) and higher than 29.6% Kimera et al (2021), Salmonella enterica (43.75%) which was lower than 58.1% as reported by Parvin et al (2020) and Klebsiella Richard et al Antibacterial Resistance and Phenotypic Detection of Extended Spectrum pneumoniae (66.7%) was higher than 45.5% in the study conducted by Kimera et al (2021).…”
Section: Discussionmentioning
confidence: 66%
“…The occurrence of ESBL producing Enterobacteriaceae isolates in our study suggest that the enzymes may be responsible for β-lactam resistant isolates were ESBL producers and this suggest that the resistant to β-lactam may be due to other mechanism like modification of target site of β-lactam or decrease in cellular uptake of the antibiotics. The percentage occurrence of ESBL producing Escherichia coli (36.36%) was lower than 68% Igbinosa et al (2023) and higher than 29.6% Kimera et al (2021), Salmonella enterica (43.75%) which was lower than 58.1% as reported by Parvin et al (2020) and Klebsiella Richard et al Antibacterial Resistance and Phenotypic Detection of Extended Spectrum pneumoniae (66.7%) was higher than 45.5% in the study conducted by Kimera et al (2021).…”
Section: Discussionmentioning
confidence: 66%
“…The development of betalactamases enzymes may be the cause of amoxicillinclavulanate resistance [16]. Moreover, the presence of extended-spectrum β-lactamase has been identified as the primary source of multiple resistance in E. coli [17]. The most common mechanism of cotrimoxazole resistance is the acquisition of plasmid-encoded, variant diaminopyrimidinefolatereductase enzymes [18], whereas the relatively high rates of gentamycin resistance in this study are most likely due to the antibiotic's indiscriminate use.…”
Section: Discussionmentioning
confidence: 75%
“…The pooled prevalence of ESBL enzyme production among Enterobacteriaceae in wastewater was 24.8% [ 52 ]. Another report in Nigeria indicated that the waste from the farm was one source of ESBL enzyme-producing bacterial contamination of vegetables [ 59 ]. Therefore, this evidence indicated that waste from farms can be the source of not only infection but also AMR bacteria.…”
Section: Discussionmentioning
confidence: 99%